2004
DOI: 10.1016/j.cub.2004.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Cell Intercalation during Tracheal Morphogenesis in Drosophila

Abstract: Tracheal morphogenesis is regulated by an interplay of different signaling systems that control cell migration and cell intercalation, respectively. Only the combined action of these signaling systems allows efficient branch elongation and the formation of morphologically distinct branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
164
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(171 citation statements)
references
References 43 publications
6
164
0
1
Order By: Relevance
“…These studies have shown that highly controlled cell intercalations, which require extensive AJ remodelling, are key to the formation of fine tracheal branches. Based on these studies and on single-cell analysis, a four-step model of tube remodelling has been proposed (Ribeiro et al, 2004) (see Fig. 5).…”
Section: The Role Of Cell Intercalationmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have shown that highly controlled cell intercalations, which require extensive AJ remodelling, are key to the formation of fine tracheal branches. Based on these studies and on single-cell analysis, a four-step model of tube remodelling has been proposed (Ribeiro et al, 2004) (see Fig. 5).…”
Section: The Role Of Cell Intercalationmentioning
confidence: 99%
“…The dorsal trunk is also the only tracheal tube in which all cells express the zinc finger transcription factor Sal (Kuhnlein and Schuh, 1996). Loss-and gain-of-function genetic studies, including single-cell analyses (Ribeiro et al, 2004), have demonstrated that Sal is indeed responsible for inhibiting cell intercalation and the formation of autocellular AJs in the dorsal trunk, and it can potently and completely inhibit intercalation when ectopically expressed in dorsal branches. How Sal inhibits intercalation remains unknown.…”
Section: The Role Of Cell Intercalationmentioning
confidence: 99%
See 2 more Smart Citations
“…First, tracheal tip cells (TCs) begin to migrate away from the tracheal sac and pull along several tracheal stalk cells into the developing branch, forming a small bud (Samakovlis et al, 1996). In a second phase, the branches elongate and narrow down due to stalk cell intercalation (SCI) and extensive cell lengthening (Ribeiro et al, 2004) (Fig. S1B).…”
Section: Introductionmentioning
confidence: 99%